Plant growth, nutrient content and water use of rubber (Hevea brasiliensis) seedlings grown using root trainers and different irrigation systems - Nabayi, Abba; Teh, Christopher Boon Sung; Mohd Hanif, Ahmad Husni; Sulaiman, Zulkefly (Universiti Putra Malaysia Press, 2018)
Rubber seedlings raised in the soil-polybag system experience root coiling and restriction and the overhead sprinkler results in much water wastage. The objective of the study was to determine the influence of root trainers and three irrigation systems on rubber seedlings grown in a peat-based medium. The irrigation systems were the overhead sprinkler (SPR), drip (DRP) and capillary wick (WCK). The fourth treatment was the control (CTRL), which required growing rubber seedlings in conventional soil-polybags that were then irrigated using the wick system. The treatments were compared with one another in terms of their influence on nutrient loss, crop water productivity and water use efficiency, plant growth parameters and plant nutrient content of the rubber seedlings. A field experiment was carried out in a rain shelter for eight months, and data collection was carried out once per month. The experimental layout was the completely randomised block design. The results showed that WCK had the lowest cumulative leachate volume and the least cumulative nutrients leached. Both DRP and WCK had the highest plant growth parameters such as total fresh and dry weight, total leaf area and girth size, water productivity and leaf nutrient content. WCK was the best irrigation system together with the peat-based growing medium for raising rubber nursery seedlings.